The Influence of Socioeconomic Status on Esophageal Cancer in Taiwan: A Population-Based Study - Chen, Hao-Yun; Chen, I-Chieh; Chen, Yi-Huei; Chen, Chi-Chang; Chuang, Cheng-Yen; Lin, Ching-Heng (Journal of personalized medicine, 2022)
Background: Esophageal cancer has extreme worldwide demographic and histologic variations in occurrence; thus, understanding the pathogenesis of esophageal cancer must be region- or country-based. We examined the incidence and tumor stage at diagnosis of esophageal cancer in relation to patients’ socioeconomic status (SES) in Taiwan. Method: This retrospective cohort study used data from Taiwan’s National Health Insurance Research Database and Taiwan Cancer Registry collected between January 2008 and December 2014. The records of 40- to 79-year-old patients diagnosed with esophageal cancer were retrieved. The distribution of the crude incidence rates of esophageal cancer by occupation and income variables was studied retrospectively. Cox proportional hazard model was used to adjust for potential confounders and compare the esophageal cancer incidence among four independent variables: age, gender, occupation, and income. Logistic regression analysis was applied to find the power of the independent variables on the odds ratio of late-stage presentation. Results: The analysis included 7763 subjects. Esophageal squamous cell carcinoma (ESCC) was the predominant histological type (96.6%) and 94.4% of patients were male. The peak affected age for ESCC was 50 to 59 years, whereas the risk of esophageal adenocarcinoma increased progressively with age. The risk of ESCC was significantly unfavorable for the most disadvantaged group, either in occupation or income, while in EAC, risk was unrelated to either factor. The stage of cancer at diagnosis was lower in the highest income groups than in the other two groups. Conclusion: Significant SES disparities in esophageal cancer incidence, based on occupation and income, are present in Taiwan. Low SES populations have a higher percentage of late-stage diagnosis. Resolution of the increasing socioeconomic disparities and narrowing the gaps in health inequities in Taiwan are needed.